Critical Care Extension Services: implications for Nursing - Galarce Vargas, Francisco Javier (2018)
The Intensive Care Unit (ICU) is characterized by treating patients of extreme severity, where the care premium in its entirety. The UCI, in addition, is a closed unit with limited places, where the staff that works is highly specialized, making its functions limited to it. This causes specialized care to be concentrated in intensive units, leaving the most basic units without this coverage, in such a way that the patient critically ill or in the process of decompensation has a rapid deterioration in rooms of less complexity due to lack of specific attention. A systematic search of the literature was carried out, which consists of the use of search engines and specialized databases. Finally, a narrative of the results was structured. The Critical Care Extension Services are already applied in different parts of the world, especially in Europe, Canada, Australia and Argentina, thinking about the quality of specialist care for critical patients, under this methodology. We tried to identify and describe functions, determine the structure, benefits and difficulties in the implementation of a Critical Care Extension Service in the adult patient so that in the future it can be applied to our local and national reality.